(untitled) (Journal of the College of Basic Education, 2026)
Women have not been able to obtain a decent share of senior organizational positions, although a significant progress has been made in recent years in the field of ‎women’s education and social participation in our country. The number of women in senior positions in governmental organizations in our society is very little. Governmental organizations are extremely important and play a very complex role in society. Their influence on various aspects of society is significant. Organizations play a key role in shaping society’s attitudes toward government, social culture, quality of life, and the success and stability of society. Public sector institutions are increasingly losing their ability to attract quality workers, and workers are being recruited by the private sector. This is particularly dangerous issues in developing countries. Researchers have developed a strong tendency to explain gender differences in playing managerial roles in the organizations. Some believe that it is not necessary to study gender differences, because men and women, when performing leadership roles, should only emphasize the norms and requirements of their formal roles set by the organization. In contrast, others believe that just as people are distinguished by their gender, they behave differently in leadership roles. They believe that women have a feminine style that is completely different from the masculine leadership style, which is oriented towards masculine tasks.In light of these developments, many feminist movements and international organizations have called for the strengthening of the empowerment approach. This approach is not only focuses on raising awareness among women and men, but also focuses on organizing women into organizations or associations that seek to enhance their capabilities and activate their participation in community development, particularly in the public sphere. It also seeks to enhance skills and provide women with the resources and opportunities that enable them to demonstrate their capabilities. Women’s participation in developing the governmental organizations means that they are able to express their opinions and make decisions that impact their lives, as well as influence community development policy. This study (The Developmental Role of Women in Security Institutions) attempts to identify society’s perceptions and views of women’s role in the field of work in general and the security institution in particular. Also, What are the most important problems facing women in the security institution? What are the levels of development and empowerment that women have achieved in the field of work in the security institution? What is the view of men and women and their work in the security institution